Analisis Latar Sosial Dalam Novel Tanah Air Beta Karya Sefryana Khairil - Adrianus Berek (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2023)
The main problem in this study is how the social background contained in the novel Tanah Air Beta which includes: habits of life; beliefs; outlook on life; ways of thinking and behaving; and social status of the people of ex-East Timor. The purpose of this study was to describe the social background contained in the novel Tanah Air Beta by Sefryana Khairil, based on the life skills of the ex-East Timorese people; beliefs; views on life; ways of thinking and behaving; and social status of the ex-East Timorese people. The theory used to answer the objectives and problems of this study is the theory of sociology of literature that sees literature has a relationship with reality, the extent to which literary works reflect reality. The Data of this study are words, sentences, events in the novel that show and explain the social background in the novel Homeland Beta. The results showed that the novel Tanah Air Beta by Sefryana Khairil contains the social background of the ex-East Timorese community. The social background in question is: the Social way of life of the ex-East Timorese community which includes; the habit of gardening,raising livestock,bathing in the lake together,and selling retail gasoline; belief in God as the creator; outlook on life; ways of thinking and behaving; and the social status of the ex-East Timorese community